Challenges and Strategies in Learning Reported Speech: A Study in the Nepalese Context - Mahatara Chhetry, Surendra Bahadur (Madhyabindu Journal, 2025)
Reported speech is a crucial grammatical concept, yet Nepali-speaking learners often struggle with its intricacies due to significant differences between the two languages, such as the absence of verb conjugation for tense in Nepali. A qualitative study was conducted to investigate the challenges faced by Grade XI learners in Nepal in acquiring reported speech in English, using observations of classroom interactions, interviews with teachers and students’ test for data collection methods. Fifty students ( 25 boys and 25 girls) studying in Grade XI were randomly selected for data collection. This study identified key challenges including errors in tense changes (backshift), difficulties in transforming direct questions into indirect questions, and problems with pronoun shifts. These challenges are exacerbated by factors such as limited real-world exposure, diverse learner backgrounds, and interference from the Nepali language. Based on these findings, the study recommends practical strategies to enhance the teaching and learning of reported speech, such as curriculum modifications, textbook revisions, and targeted teacher training programs that focus on addressing the specific grammatical issues identified.